Electron correlation effects in the photoionization of CO and isoelectronic diatomic molecules. Issue 4 (11th January 2019) - Ponzi, A.; Quadri, N.; Angeli, C.; Decleva, P.
Abstract : This figure shows the theoretical photoelectron spectra associated with each target molecule. This representation is useful to instantly visualize differences in the position and intensity of the examined satellite bands. Abstract : This paper investigates the first sigma satellite band, which is by far the most prominent, in the valence photoelectron spectra for a set of isoelectronic diatomic molecules: carbon monoxide, carbon monosulfide, carbon monoselenide, silicon monoxide and boron monofluoride. In particular, we analyze the effect of the electronic structure, with the change of the atomic pair along the row and column of the periodic table on the position of the satellite peak as well as on the related dynamical observables profiles. For this investigation, highly correlated calculations have been performed on the primary ionic states and the satellite band for all the molecules considered. Cross sections for the primary ionic states, calculated using Dyson orbitals, have been compared with those obtained with Hartree–Fock and Density Functional Theory to probe the impact of the correlation in the bound states on the photoionization observables. Limitations of a simple intensity borrowing mechanism clearly result from the analysis of the satellite state, characterized by different features with respect to the relevant primary states.